2020
DOI: 10.2478/rtuect-2020-0098
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Risk of the Visible Light Assisted Photocatalytical Treatment of PRD1 and T4 Bacteriophage Mixtures

Abstract: In current study UV light and visible light activated photocatalytic inactivation treatment was applied to the less commonly studied subjects, namely bacteriophages PRD1, T4 and their mixture. By using UV light irradiation and high efficiency P25 TiO2 photocatalyst powders it was demonstrated that individually and in mixture PRD1 bacteriophage is particularly vulnerable to the photocatalytic inactivation and in just approximately 20 min its infectivity is reduced by 100 %. As for the T4 bacteriophage, it has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Our earlier study with visible light activated carbon-doped TiO2 photocatalyst showed effective inactivation of PRD1 and T4 bacteriophages [38]. C-doped TiO2 traditionally has a narrower band gap and additional electron energy levels [23,24].…”
Section: Discussionmentioning
confidence: 92%
“…Our earlier study with visible light activated carbon-doped TiO2 photocatalyst showed effective inactivation of PRD1 and T4 bacteriophages [38]. C-doped TiO2 traditionally has a narrower band gap and additional electron energy levels [23,24].…”
Section: Discussionmentioning
confidence: 92%
“…____________________________________________________________________________ 2021 / 25 980 Titanium dioxide is arguably the most promising photocatalytic material. It is non-toxic and is widely used in various fields including water cleaning from organic pollutants, microorganisms and viruses [6]- [8]. Unfortunately, the band gap value of the pristine TiO2 is larger than the energy of the visible light photons.…”
Section: Environmental and Climate Technologiesmentioning
confidence: 99%